Effect of small cardamom extracts on Mutans streptococci in comparison to chlorhexidine gluconate and de-ionized water (In vitro study ( - Ibrahim, Ghada A; Al – Obaidi, Wesal A (Journal of Baghdad College of Dentistry, 2013)
Background: Herbs are being widely explored to discover alternatives to synthetic antibacterial agents.Small Cardamom often referred to as queen of spices because of its very pleasant aroma and taste, have a history as old as human race. Most people use cardamom as a spice and are largely unaware of its numerous health benefits. The purpose of this study was to evaluate the effect of different concentrations of water and alcoholic cardamom extracts on sensitivities, growth, and adherence of Mutans streptococci in vitro. Materials and Methods: In this study, saliva was collected from ten volunteers (College students 18-22 years). Agar well technique was used to study the sensitivities of Mutans streptococci to different concentrations of small cardamom extracts and other control agents, also the effects of small cardamom extracts on viable counts, adherence of Mutans streptococci were studied Results: According to agar well diffusion methods, both cardamom extracts were effective in inhibition of Mutans streptococci, but still weaker than chlorhexidine gluconate 0.2%. Alcoholic extracts showed higher zone of inhibition compared to the same concentration of water with high significance differences (P